Theories of civil violence - Rule, James B., 1943- (University of California Press, 1988)
"Theories of Civil Violence provides both a new look at the origins of civil upheaval and a critical examination of social theory itself. Rule develops an incisive historical analysis of theories of civil violence, beginning with the classic views of Hobbes and Marx and continuing to those of Gurr, Tilly and other present-day thinkers. He then exploits this overview to yield conclusions on the nature of and prospects for theoretical understanding of social and political life in general." - Book cover.
Keywords: Violence.; Riots.; Revolutions.; Violence; Riots; Revoluciones.; Tumultos.; Émeutes.; Révolutions.; violence.; revolutions.; SOCIAL SCIENCE / Sociology / General; Revolutions; Gewalt; Revolution; Soziologie; Geweld.; Revoluties.; Burgers.; Révolutions -- Philosophie -- Histoire.; Violence -- Philosophie.; Résistance politique -- Philosophie.